Doctoral Theses in Physics Education Defended in the Czech Republic from 2004 to 2013 — Overview and Analysis - Žák, Vojtěch (Scientia in educatione, 2015)
The purpose of the study is to analyse doctoral theses (dissertations) in the didactics of physics (physics education) defended in the Czech Republic in recent years. The strategic goal is to reflect the development and the current state of the didactics of physics and thus to contribute to its future development (and to the development of other subject didactics). The qualitative research design was used in this research. The data were collected using an analysis of particular doctoral theses defended at Czech universities between the years 2004 and 2013. Besides the basic overview, such as the number of theses defended in particular years, this study also deals with the analysis of data collection methods used in dissertation research, the educational level at which the research questions are dealt with, physics content and the theses’ focus from the education point of view. The analysis shows that the number of defended theses has been increasing in general in recent years. The most frequently used data collection methods are questionnaires and achievement tests. The theses mainly focus on the upper secondary schools (especially secondary grammar schools) and deal with various physics areas. They are often aimed at the implementation of physics or interdisciplinary topics in school curricula (e.g. biophysics), at evaluation, and at information technology.